2018
DOI: 10.3389/fonc.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Activity as a Switch for Glioblastoma Responsiveness to Temozolomide

Abstract: RationaleThe activity of the transcription factor, hypoxia-inducible factor (HIF)-1α, is a common driver of a number of the pathways involved in the aggressiveness of glioblastomas (GBMs), and it has been suggested that the reduction in this activity observed, soon after the administration of temozolomide (TMZ), can be a biomarker of an early response in GBM models. As HIF-1α is a tightly regulated protein, studying the processes involved in its downregulation could shed new light on the mechanisms underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 54 publications
7
60
0
2
Order By: Relevance
“…In the treatment of glioma, cytotoxicity chemotherapeutics drugs including TMZ can induce autophagy, which may promote the development of treatment resistance [23][24][25]57]. In our study, we observed for the first time that ATG4C is involved in TMZ-induced autophagy, and depletion of ATG4C significantly increased the sensitivity of U87-MG and T98G cells to TMZ, which are thought to be TMZ sensitivity and resistance cells, respectively [58]. Selective and specific cytotoxicity to tumor cells is expected during glioma chemotherapy, which can increase the anti-tumor activity of TMZ with less toxic effects.…”
Section: Discussionsupporting
confidence: 49%
“…In the treatment of glioma, cytotoxicity chemotherapeutics drugs including TMZ can induce autophagy, which may promote the development of treatment resistance [23][24][25]57]. In our study, we observed for the first time that ATG4C is involved in TMZ-induced autophagy, and depletion of ATG4C significantly increased the sensitivity of U87-MG and T98G cells to TMZ, which are thought to be TMZ sensitivity and resistance cells, respectively [58]. Selective and specific cytotoxicity to tumor cells is expected during glioma chemotherapy, which can increase the anti-tumor activity of TMZ with less toxic effects.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, quantitative proteomics analysis of isolated lysosomes from CMA-activated conditions in cancer cells has recently revealed a new role for CMA in the control of cell translation [114]. Importantly, up-regulated CMA may also assist chemoresistance of GB, making them more resistant to different stressors such as oxidative stress, hypoxia or even DNA damage agents [4,115]. Up-regulation of CMA in GB cells that are in contact with perivascular areas, not only favors their proliferation, but it may even interfere with the aberrant CMA up-regulation in tumor surrounding cells that benefits tumor survival and affects anti-tumor immune microenvironment responses [36].…”
Section: Functionsmentioning
confidence: 99%
“…Many recent studies have provided convincing evidence of strong correlations between elevated levels of HIF-1α and tumor metastasis, angiogenesis, and tumor resistance to therapy [14][15][16]. Emerging evidence suggests that HIF-1α inhibitors used in combination with standard chemotherapy improve the response of TMZ-resistant GBM cells [17]. Furthermore, silencing HIF-1α expression appears to inhibit the proliferation [18], invasion, and migration of GBM [19].…”
mentioning
confidence: 99%